Knowledge, attitude, and practice toward coronary heart disease secondary prevention among coronary heart disease patients in Shanghai, China - Hao Wang; Bo Wu; Wenqi Guan; Tan Zhou; Hongbao Wang; Wei Li; Xueqin He (PLoS ONE, 2025)
Background This study aimed to investigate knowledge, attitude, and practice (KAP) toward coronary heart disease (CHD) secondary prevention among CHD patients. Methods This web-based cross-sectional study enrolled patients with CHD who visited the Yangpu District Central Hospital in Shanghai (China) between October 18, 2022, and March 25, 2023. The administered questionnaire assessed demographic information and KAP; factors associated with good practice were identified by multivariate logistic regression. Results A total of 507 participants were included in the study, with 361 (71.2%) being male. In terms of education, 125 (24.7%) had a junior high school level or below. The mean scores for knowledge, attitudes, and practices were 31.28 ± 7.30 (possible range: 0–42), 54.09 ± 3.33 (possible range: 12–60), and 35.48 ± 3.36 (possible range: 11–55), respectively. For specific knowledge items on CHD, 57.6% of participants correctly identified that women are more susceptible to CHD. Physical labor and emotional excitement as triggers for CHD were correctly recognized by 94.1%. The need for long-term medication and follow-up after a CHD diagnosis had the highest correctness rate at 98.8%. Additionally, 84.6% correctly understood that recurrence of CHD is possible after PCI surgery. Multivariate analysis indicated that smoking and diabetes status were significantly associated with Practice scores. Current smokers reported lower practice levels than never smokers (OR = 2.858, 95% CI: 1.442–5.662, P = 0.003). Participants with diabetes reported higher practice levels than those without diabetes (OR = 4.169, 95% CI: 2.329–7.463, P < 0.001). Conclusions Patients with CHD in Shanghai, China, demonstrated good knowledge and positive attitudes toward CHD secondary prevention, although there were some gaps in actual practice behaviors. Enhancing targeted educational interventions and support systems in clinical settings may help bridge these gaps and improve adherence to recommended preventive practices.